Modeling the micro-explosion of miscible and immiscible liquid droplets - Antonov, D.V.; Fedorenko, R.M.; Kuznetsov, G.V.; Strizhak, P.A. (Acta astronautica, 2020)
The research subjects are immiscible two-component droplets containing combustible and non-combustible liquids with a clear interface, as well as emulsion droplets. The key limitations are identified for the current models unable to adequately describe the critical (threshold) conditions and characteristics of micro-explosion. Experiments are conducted to obtain the heating times until breakup (delay times) and critical (threshold) temperatures triggering the droplet breakup. Two methods are used: a droplet is either suspended on a holder and placed into the heating chamber or it free-falls in a tubular muffle furnace. The developed models reliably describe the processes under study when two threshold conditions of droplet breakup are used: non-combustible component reaching its boiling temperature at the inter-component interface and a bubble or a group of bubbles in a droplet growing in size beyond critical values. In the experiments, the heating temperature ranges from 500 to 1400 K, the initial droplet size is between 1 and 3 mm, and the relative volume concentrations of the components are varied in the range of 10–90 vol%. An acceptable agreement has been established for the key heating and fragmentation characteristics at various heating temperatures and with component compositions of heterogeneous droplets. The maximum deviations of the theoretical droplet breakup times from the experimental ones do not exceed 40%. For critical (minimum and maximum) heating temperatures of the external medium sufficient for breakup, the deviations of theoretical and experimental data do not exceed 50 K. The study defines the conditions, in which the newly developed models can reliably predict the characteristics of micro-explosive droplet breakup. Hypotheses have been formulated explaining the differences between theoretical and experimental characteristics of micro-explosive droplet breakup. The research findings enable to outline the promising ways to improve micro-explosive breakup models for their further use in the secondary atomization of heterogeneous liquids, for instance, to develop the technologies of fuel ignition, thermal and flame water treatments, etc. [Display omitted] •Two types of models are considered with different micro-explosion criteria.•Temperature at inter-component interface under micro-explosion reaches 360–370 K.•A 2–3-fold increase of droplet size due to vapor bubbles is enough for breakup.•Local overheating of water and nucleation near the droplet surface are main processes.•Most of micro-explosion delay time is the time of droplet heating until it boiling.